Réparer l’injustice d’un châtiment par l’oubli : l’amnistie de soldats du régiment suisse de Châteauvieux (31 décembre 1791) - Stanislas de Chabalier (Criminocorpus)
In September 1790, the cruel punishment, by a military council of their country, inflicted upon Swiss soldiers filled many contemporaries with indignation. These men, who were engaged in the French armies, rose up with the Nancy garrison in August 1790. The National Constituent Assembly then endorsed their repression and admitted the decision of the Swiss military justice which condemned them to death or to the galleys. However, slightly more than a year later, the deputies of the new Legislative assembly amnestied them and spoke up against the treatment they suffered. Long debates in the Assembly show that with this decree of amnesty, parliament members take a stand against the severity of the sentence the Swiss soldiers have endured. Thus conceived and applied, the Amnesty Law makes it possible to set right an injustice and to show the humanity of those who conceived this.